Pelatihan Penggunaan Canva dan Google Drive Bagi Masyarakat Desa Wijirejo Kecamatan Pandak Kabupaten Bantul - Murinto Murinto; Lisdianto Dwi Kesumahadi; Zulhaji Guswantoro (Journal of Community Development, 2023)
Specifically for the Gesikan IV area, Wijrirejo Village, there are also mosque youth. One of the programs is to develop and enhance and create the competitiveness of members so as to create superior youth accompanied by the use of technology to improve the quality of publications and documentation in supporting daily life. The problem that occurs is that not all members have the ability to use graphic design applications to make posters. Mosque youth experience difficulties in teaching graphic design applications as is currently the case, this is because youth organizations do not yet have graphic design skills. Likewise, the use of other applications in cloud-based storage, namely Google Drive. By looking at these problems, in this service there will be training on the use of graphic design applications for making posters using Canva and cloud-based storage applications using Google Drive in the Wijirejo Village area, especially Padukuhan Gesikan IV, Pandak District, Bantul Regency. The method used in this service is pre-implementation, training, mentoring and evaluation. Two students were directly involved in this PPM, namely Zulhaji Guswantoro and Lisdianto Dwi K, undergraduate students of the Informatics Study Program. Pre-implementation includes making Canva and Google Drive modules and communicating with partners regarding what needs are needed in poster making and Google Drive training. The training is hands-on practice carried out to increase youth skills in operating the Canva application for making posters and Google Drive for cloud-based storage applications. The implementation method is Offline. This training was held for 2 days starting February 28 and March 1 2023 from 15.00 to 17.00 and took place at the Baitul Ummah Mosque, Wijirejo Village. Assistance is carried out to assist youth in making posters using Canva and using cloud-based storage applications using Google Drive. Evaluation is used to make improvements for the next service. The results of this dedication are posters made using the Canva application and the ability to store data using Google Drive. With this training, 85% of teenagers found it easier to use the Canva and Google Drive applications, and found it helpful to use the application for making posters and storing data in the cloud. The output of this PPM includes training modules, articles published in online KR and Print KR